Essays on Food Security in Sub-Saharan Africa : the role of food prices and climate shocks - (:unkn) unknown (My University, 2014)
This doctoral thesis is in line with the renewed interest in research on agriculture and food security, following the 2008 global food crisis. The aim of this thesis is to contribute to a better understanding of the complex issues surrounding food security. The first chapter investigates whether the changes in the international price of rice are transmitted to the domestic prices of rice in Senegal, Mali and Chad. Results indicate that the domestic prices of imported rice in Dakar and of local rice in Bamako react differently to changes in the world price depending on whether the world price is rising or falling. Chapter 2 analyses by how much trade barriers at the border and transport costs impede the integration of agricultural markets in West and Central Africa. Results highlight the role played by borders in explaining price deviations between markets. Additionally, belonging to an economic union and sharingthe same currency appear as major determinants of market integration. The third chapter aims at providing new early warning indicators based on food prices in Mali, Niger and Burkina Faso. Our analysis reveals that price crisis can be predicted about 6 months in advance through the observation of past price movements. Chapter 4 focuses on the analysis of children’s vulnerability to climate shocks in Burkina Faso. By combining health data originating from a 2008 household survey with meteorological data, we show the importance of weather conditions in prenatal period and in the first year of life on the future nutritional status of the children.
Keywords: African Research